Thermally Conductive Ti3C2Tx Fibers with Superior Electrical Conductivity - Zhou, Yuxiao; Zhang, Yali; Pang, Yuheng; Guo, Hua; Guo, Yongqiang; Li, Mukun; Shi, Xuetao; Gu, Junwei (Nano-Micro Letters, 2025)
High-performance Ti3C2Tx fibers have garnered significant potential for smart fibers enabled fabrics. Nonetheless, a major challenge hindering their widespread use is the lack of strong interlayer interactions between Ti3C2Tx nanosheets within fibers, which restricts their properties. Herein, a versatile strategy is proposed to construct wet-spun Ti3C2Tx fibers, in which trace amounts of borate form strong interlayer crosslinking between Ti3C2Tx nanosheets to significantly enhance interactions as supported by density functional theory calculations, thereby reducing interlayer spacing, diminishing microscopic voids and promoting orientation of the nanosheets. The resultant Ti3C2Tx fibers exhibit exceptional electrical conductivity of 7781 S cm−1 and mechanical properties, including tensile strength of 188.72 MPa and Young’s modulus of 52.42 GPa. Notably, employing equilibrium molecular dynamics simulations, finite element analysis, and cross-wire geometry method, it is revealed that such crosslinking also effectively lowers interfacial thermal resistance and ultimately elevates thermal conductivity of Ti3C2Tx fibers to 13 W m−1 K−1, marking the first systematic study on thermal conductivity of Ti3C2Tx fibers. The simple and efficient interlayer crosslinking enhancement strategy not only enables the construction of thermal conductivity Ti3C2Tx fibers with high electrical conductivity for smart textiles, but also offers a scalable approach for assembling other nanomaterials into multifunctional fibers. Highlights: 1 The strong covalent crosslinking between trace amounts of borates and the hydroxyl groups of Ti3C2Tx significantly reduces interlayer spacing, enhances orientation and compactness, leading to notable improvements in both the mechanical (tensile strength of 188.72 MPa) and electrical properties (7781 S cm−1) of Ti3C2Tx fibers. 2 Trace amounts of borates can promote the regularization of interfacial structures, reduce interfacial thermal resistance, and significantly enhance the thermal conductivity (13 W m−1 K−1) of Ti3C2Tx fibers, thus increasing their potential for efficient heat transfer applications.